A DEVELOPMENT OF THE CAUSAL MODEL BASED ON THE RESEARCH PRODUCTIVITY OF THE INSTRUCTORS, KASETSART UNIVERSITY KAMPHAENGSAEN CAMPUS - Dhanajyaitsadej, Bhumipat; Moungpara, Pajongjit (Academic Journal of Thailand National Sports University, 2022)
The purposes of this study were to develop and to verify the coherence of the causal model of research productivity using empirical data. This study also examined the direct and indirect effects on the research productivity of instructors, Kasetsart University at the Kamphaengsaen Campus. Using a stratified random sampling method, the sample consisted of 340 instructors who worked at Kasetsart University Kamphaeng Saen Campus during the 2018 academic year. Cronbach’s alpha coefficient was found to be between 0.887 and 0.962 in the research instrument, as a questionnaire about factors influencing research productivity. The descriptive statistic and the linear structural equation model were used to analyze the data. Results showed that 1) the causal model of research productivity of the instructors at Kasetsart University Kamphaengsaen campus consisted of two external latent variables namely individual background and environment factors as well as three internal latent variables namely attitude toward research, research motivation, and research productivity, and 17 observed variables, as well as 2) The model had consistency with the empirical data (χ2 = 218.75, p = .052, RMSEA = 0.033, NFI = 0.94, CFI = 0.92, GFI = 0.94, RMR = 0.034, CN = 232.62 ), and 3) the factors influencing entirely research productivity effects, research motivation had a direct effect of 0.66, attitude toward research had a direct effect of 0.61, individual factor had a direct effect of 0.60, and environmental factor had a direct effect of 0.59.